KOMUNIKASI KELOMPOK DI DALAM RUMAH REHABILITASI KELUARGA KEMBANG CAHAYA - Prewitasari, Kuswidianti Dharma; Novianti, Wiwik Novianti (Jurnal InterAct, 2019)
During this millennial era, the rise of drug abuse is increasingly worrying. Many users or addicts actually come from children who are still underage. This is certainly a serious problem for the government, society and the Indonesian people. The purpose of this study is to find out more about how the pattern of group communication is carried out in the rehabilitation center for former drug addicts. This research method uses a descriptive qualitative approach with data collection techniques through observation and interviews. One of the rehabilitation sites for former drug addicts is located in the city of Purwokerto, Banyumas, Central Java. The place is a rehabilitation house under the name Kembang Cahaya Family Community (Kekaca). This community is a community engaged in the social field with a focus on helping former drug addicts in the healing process after drug use. The results of this study indicate that the existence of a community such as Kekaca can be a solution and a breath of fresh air for former drug addicts who want to recover through a community that is engaged in the focus of rehabilitation for former drug addicts. The conclusion is that by using a family communication pattern in the healing process carried out in the Keluarga Kembang Cahaya (Kekaca) community, it is considered effective as one of the efforts taken to help the healing process totally after drug use.